УДОСКОНАЛЕННЯ ЛАНДШАФТНО- РЕКРЕАЦІЙНОГО СЕРЕДОВИЩА МІСТ ТА ПОЗАМІСЬКИХ ТЕРИТОРІЙ ШЛЯХОМ ВПРОВАДЖЕННЯ ВЕЛОСИПЕДНОЇ ІНФРАСТРУКТУРИ (World Science, 2018)
The classification of urban and suburban landscapes and recreation objects is given, and the expediency of using cycling transport as an independent within the territory of green plantations and transit in the general system of the city bicycle network is analyzed. Estimates of the number of parking lots for bicycles in city parks of different sizes are given. The results of the study are illustrated by the introduction of a project for the reconstruction of the park of culture and recreation them. M. Rylsky in Kyiv, Ukraine. Quantitative and qualitative indicators of improving the landscape and recreational environment of cities and outlying areas are identified by introducing bicycle infrastructure: normative data, radii of accessibility to destinations and services, the possibility of changing the type of operation and mode of operation from the capacity and conditions of the inhabitants' activity depending on the season and season load on city objects; the efficiency of communications in remote networks, functional optimality, convenience of communication, strengthening of the connection of the city with natural resources.